An integrated and comprehensive transcriptome reveals immune‐related genes and signal pathways in topmouth culter (Culter alburnus). (20th April 2016) - Lei, Shuangyong; Chen, Xiaowen; Wang, Jun; Zhou, Lu; Zhang, Youliang; Zhang, Guoqi; Lu, Guoqing; Wang, Chenghui
Abstract: Topmouth culter ( Culter alburnus ) is an important freshwater species in China. In recent years, the population of topmouth culter has declined sharply due to the increasing pollution, overfishing and habitat destruction. It may lead to adverse effects, including weakening health, causing disease, and reducing the quality of topmouth culter. It is urgent to conduct resource management, protection and genetic improvement strategies in topmouth culter, especially develop genetic breeding program with disease resistance. In this study, we applied RNA‐seq technology to de novo assemble a comprehensive transcriptome, and to discover immune‐related genes and pathways in topmouth culter. A total of 102 017 transcripts were assembled with an average length of 945 bp, of which 45 482 protein coding sequences were predicted. BLAST search resulted in 53 575 and 45 602 transcripts with homologous sequences in NCBI‐NR and UniProt respectively. Further functional analysis identified 24 052 transcripts in Gene Ontology (GO) categories and 19 260 transcripts in KEGG pathways. Significantly, 13 immune‐related pathways with 524 immune‐related genes were identified. Our data provided an integrated and comprehensive transcriptome resource for topmouth culter, which could be essential for further research in selective breeding of disease resistance, functional genomics, and genome editing of topmouth culter.